THE EFFECT OF USING PICTURE SERIES TO IMPROVE STUDENTS’ WRITING SKILL IN DESCRIPTIVE TEXT AT EIGHTH GRADE STUDENTS OF SMP SWASTA HKBP BATU 4 SIANTAR - Josua Lumbantobing (Jurnal Intelek Insan Cendikia, 2025)
This study explores the impact of using picture series as a teaching aid on descriptive writing skills of eighth grade students at SMP Swasta HKBP Batu 4 Siantar. This study used a quasi-experimental design, involving an experimental group taught using picture series and a control group taught using conventional methods. A total of 60 students participated, with 30 students in each group. Pre-test and post-test were given to evaluate students' writing skills in terms of content, organization, vocabulary, grammar, and writing mechanics. The results showed a significant increase in students' writing skills in the experimental group, confirming that picture series can improve students' creativity, vocabulary use, and engagement in writing tasks. These results indicate that picture series is an effective visual learning media in teaching English at the junior high school level.